2018
DOI: 10.1080/08997764.2020.1849228
|View full text |Cite
|
Sign up to set email alerts
|

The economics of social media (super-)stars: an empirical investigation of stardom and success on YouTube

Abstract: A new type of superstars developed with the rise of social media markets: social media superstars (SMS). The economic literature on the superstar phenomenon provides empirical evidence on different types of stars, above all athletes and musicians. This paper presents the first empirical work on SMS with original data from YouTube. Using various econometric techniques, we analyze a unique sample of 200 YouTube stars out of four different video categories to shed light on this new phenomenon. Beyond applying cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 56 publications
2
21
0
Order By: Relevance
“…), i.e., a sort of user-exchange of contents, and professional contents from business companies are in the clear minority. The nature of YouTube's early 'user generated content' (from users for users) has changed a lot and initial 'private' uploaders professionalized towards being active content providers, offering regular video uploads regarding specific topics according to the channel's media concept (Döring 2014;Budzinski and Gaenssle 2020). Notwithstanding the still existing type of non-professional content, this trend of professionalization points towards the significant turnovers and revenues that content providers such as so-called social media stars 4 earn through participation on YouTube's advertisement revenues as well as through product placements-with the latter further emphasizing the commercial nature of the content supply (Budzinski and Gaenssle 2020;Gaenssle and Budzinski 2021).…”
Section: Fundamental Differences In Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…), i.e., a sort of user-exchange of contents, and professional contents from business companies are in the clear minority. The nature of YouTube's early 'user generated content' (from users for users) has changed a lot and initial 'private' uploaders professionalized towards being active content providers, offering regular video uploads regarding specific topics according to the channel's media concept (Döring 2014;Budzinski and Gaenssle 2020). Notwithstanding the still existing type of non-professional content, this trend of professionalization points towards the significant turnovers and revenues that content providers such as so-called social media stars 4 earn through participation on YouTube's advertisement revenues as well as through product placements-with the latter further emphasizing the commercial nature of the content supply (Budzinski and Gaenssle 2020;Gaenssle and Budzinski 2021).…”
Section: Fundamental Differences In Contentmentioning
confidence: 99%
“…The nature of YouTube's early 'user generated content' (from users for users) has changed a lot and initial 'private' uploaders professionalized towards being active content providers, offering regular video uploads regarding specific topics according to the channel's media concept (Döring 2014;Budzinski and Gaenssle 2020). Notwithstanding the still existing type of non-professional content, this trend of professionalization points towards the significant turnovers and revenues that content providers such as so-called social media stars 4 earn through participation on YouTube's advertisement revenues as well as through product placements-with the latter further emphasizing the commercial nature of the content supply (Budzinski and Gaenssle 2020;Gaenssle and Budzinski 2021). Nowadays, a significant share, if not most of the views on YouTube, fall on commercial content, most of which is professionally produced; the most popular 20% receive 97% of views (Ding et al 2011) and 10-30% of videos have fewer than ten views (Chowdhury & Makaroff 2013).…”
Section: Fundamental Differences In Contentmentioning
confidence: 99%
“…Reputation Correlation [7], [45], [55], Show some evidence of correlation between past reputation and current Bias Study [46], [37], [8] success [7,45,55,46,37,8].…”
Section: Approach References Summarymentioning
confidence: 99%
“…Reputation Bias. Prior works on online reputation suggest that past reputation may be useful in predicting current success [7,45,55,46,37,8] (also known as "superstar economics" [39]). Beuscart et al [7] observed that in MySpace Music, most of the audience is focused on a few stars.…”
Section: Socialmentioning
confidence: 99%
See 1 more Smart Citation